Gamma Spectrometric Analysis of Natural Radionuclides and Radiological Hazards in Ilmenite Sand - Esther Mutiara Santallum Ekklesia Tibalia; Farida Diyah Hapsari; Tamaratritania Citta Trisnantari; Geraldi Rahanra; Muhammad Ikhsan Taipabu (Program studi Teknik Kimia UNS, 2026)
Ilmenite sand, categorized as Naturally Occurring Radioactive Material (NORM), contains radionuclides derived from the uranium and thorium decay series. The present work investigates radionuclide concentrations in ilmenite sand collected from a mineral processing facility to evaluate associated radiological hazards using gamma spectrometry. Activity measurements were performed with a gamma spectrometry system calibrated for energy and efficiency using a Eu-152 reference source. Environmental background radiation was measured separately to correct spectral data during analysis. Prior to measurement, samples were dried, homogenized, and sealed in airtight containers to establish radioactive equilibrium between parent radionuclides and their progeny. Radionuclide activities were quantified based on characteristic gamma-ray peak energies. The measured activity concentrations were 472.98 Bq/kg for Ra-226, 302.20 Bq/kg for Th-232, and 10.68 Bq/kg for K-40. Radiological hazard parameters, including radium equivalent activity (Raeq), external hazard index (Hex), internal hazard index (Hin), and absorbed dose rate, were subsequently calculated. The estimated annual effective dose was 0.492 mSv/year, remaining below the recommended public exposure limit of 1 mSv/year. These findings indicate that, despite relatively elevated radionuclide activities, the resulting radiation exposure levels remain within acceptable safety limits. Overall, gamma spectrometry demonstrates reliable capability for radionuclide identification and radiological risk assessment in mineral-based materials.